1991
DOI: 10.1002/pola.1991.080290311
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the formation of poly(ethylene terephthalate) with model molecules. IV. Catalysis of the esterification of ethylene glycol with benzoic acid and of the condensation of ethylene glycol monobenzoate

Abstract: The esterfication of ethylene glycol (EG) with benzoic acid (BA) is an acid‐catalyzed reaction which leads, as a first intermediate, to ethylene glycol monobenzoate (EGMB). This compound has an OH group which is more active towards carboxylic groups than the first OH group of EG. Moreover, it is a key intermediate in the formation of sideproducts containing diethylene glycol (DEG) moieties. The condensation reaction of EGMB was particularly studied in the presence of carboxylic acids or metal derivatives as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The formation of strong complexes between EG and antimony has frequently been proposed to explain the low catalytic activity of this metal in alcohol-rich medium. 284,285 The presence of carboxyl groups has also been reported to inhibit the catalytic activity of various acetates and alkoxides. A reasonable mechanism should involve the coordination of the ester carbonyl to the metal atom, favoring the nucleophilic attack of alkoxy ligands or hydroxyl endgroups on the corresponding carbon.…”
Section: Reaction Mechanisms and Catalysismentioning
confidence: 99%
“…The formation of strong complexes between EG and antimony has frequently been proposed to explain the low catalytic activity of this metal in alcohol-rich medium. 284,285 The presence of carboxyl groups has also been reported to inhibit the catalytic activity of various acetates and alkoxides. A reasonable mechanism should involve the coordination of the ester carbonyl to the metal atom, favoring the nucleophilic attack of alkoxy ligands or hydroxyl endgroups on the corresponding carbon.…”
Section: Reaction Mechanisms and Catalysismentioning
confidence: 99%
“…Calculations of the equilibrium constants for the system water, EG, DEG, and dioxane showed that dioxane is the most stable species in this system. More recent publications [24,38,57,59], however, favour the formation of DEG by direct etherification, which is condensation of two hydroxyl groups as 2R-OH → R-O-R + H 2 O. In the above temperature range, the equilibrium constant for the formation of DEG from EG is significantly lower, as shown in Figure 2.11.…”
Section: Formation Of Diethylene Glycol and Dioxanementioning
confidence: 90%
“…It is generally accepted that compounds of antimony, tin and titanium are the most active catalysts for polycondensation. Otton and co-workers [18,[36][37][38] performed extensive studies on the catalyzed formation of PET with model systems. Hovenkamp [35] found that the latter catalysts are very active in media having both high and low hydroxyl group contents, but are easily poisoned by traces of carboxylic groups.…”
Section: Transesterification/glycolysismentioning
confidence: 99%
See 1 more Smart Citation
“…P E T prepolymer (DP of [1][2][3][4][5] is obtained from the esterification step and the prepolymer is processed for polycondensation at more severe conditions to obtain higher molecular weight, such as low pressure in the presence of a catalyst.…”
Section: -S995/96/071033-07mentioning
confidence: 99%